Pertumbuhan Tanaman Kakao (Theobroma cacao L.) Belum Menghasilkan pada Pemberian Pupuk NPK Phonska - Purwati Purwati (Agrifarm : Jurnal Ilmu Pertanian, 2019)
The aim of the study was to determine the growth of immature cocoa plants in the provision of NPK phonka fertilizer. This research was conducted from February to May 2016 in North Samarinda District, East Kalimantan. The study used a randomized block design with five replications. The treatment of NPK Phonska fertilizer (N) consists of 3 levels, namely control (n0), 250 g / plant (n1), 500 g / plant (n2). Data were analyzed statistically and tested further with the smallest significant difference test (LSD) at the level of 5%. The results showed that the best growth of cocoa plants was the administration of Phonska NPK 500 g / plant.